Activist communication: a critical reflection on an ethnographic research project - Wolf, Katharina (Australian and New Zealand Communication Association, 2011)
Critical scholars have questioned the widespread assumption that public relations’ focus is solely on achieving corporate goals, arguing that this perspective does not only undermine the standing of public relations as a critical scholarly discipline in its own right, but furthermore limits the understanding and value of professional communication in general. This argument is highlighted in the discipline’s focus on activist communication, which has developed into one of the largest bodies of knowledge in public relations research. However, despite extensive scholarly interest, spanning over more than three decades, to date little emic research has been conducted to provide insight into activist communication. This paper has a methodological focus and consists of a review of and critical reflection on a postgraduate research project that set out to address this existing gap, by studying one of the currently most active activist groups in Australia: the WA anti nuclear movement. Using ethnographic techniques, the author conducted semi-structured interviews, undertook participant observation at a range of activist events and spent time at the movement’s umbrella organisation’s offices. This paper discusses challenges and benefits of the research experience so far, by engaging with ethnographic and social movement literature as well as by drawing on Pierre Bourdieu’s notion of reflexivity. The author concludes by suggesting that public relations as a discipline can be enriched by research that departs from a corporate perspective, to one that focuses on alternative voices and viewpoints.